1997
DOI: 10.1523/jneurosci.17-18-07045.1997
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Transport Blockade in the Neonatal Rat Optic Nerve Induces Limited Retinal Ganglion Cell Death

Abstract: Optic nerve section in the newborn rat results in a rapid apoptotic degeneration of most axotomized retinal ganglion cells (RGCs). This massive process of neuronal death has been ascribed mainly to the interruption of a trophic factor supply from target structures rather than to the axonal damage per se. To distinguish between these two possibilities, we induced a reversible axonal transport blockade in the developing optic nerve by topical application of a local anesthetic (lidocaine). Light and electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…39 Here, we addressed this problem by recording the PERG-a signal that depends on the physiologic integrity of RGC-before and after manipulations at postretinal level that impair retrograde signaling in the retinocollicular pathway. Lidocaine is a well established method to block axon transport [40][41][42] without damaging optic nerve structures, 43 and acts at very low concentrations. 44 At sufficient concentrations, lidocaine also is known to alter signal conduction by blocking voltage-gated sodium channels in the neuronal cell membrane, 45 thereby suppressing postsynaptic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Here, we addressed this problem by recording the PERG-a signal that depends on the physiologic integrity of RGC-before and after manipulations at postretinal level that impair retrograde signaling in the retinocollicular pathway. Lidocaine is a well established method to block axon transport [40][41][42] without damaging optic nerve structures, 43 and acts at very low concentrations. 44 At sufficient concentrations, lidocaine also is known to alter signal conduction by blocking voltage-gated sodium channels in the neuronal cell membrane, 45 thereby suppressing postsynaptic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Reversible blockade of axon transport was not expected to cause damage to RGC, 43,46 whereas for optic nerve crush RGC loss was expected to start approximately 5 days after surgery. 21,47 However, the effects of the optic nerve crush could include an acute physiologic effect on RGC signaling 48 that added to the effect mediated by impairment of retrograde signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Because of good surgical accessibility, lesion of the retinocollicular projection in the rat serves as a convenient model to study secondary death of injured CNS neurons (Villegas-Pérez et al, 1988Eschweiler and Bähr 1993;Mey and Thanos, 1993;Mansour-Robaey et al, 1994). In comparison with lesion models in newborn rats, transection of the adult ON holds the advantage that injury-induced RGC loss is not confounded by additional RGC degeneration attributable to deprivation of target-derived trophic support during the period of naturally occurring cell death (C arpenter et al, 1986;Fagiolini et al, 1997). For this reason, axotomy of the ON in the adult rat, a model with well documented spatiotemporal kinetics of cell loss, better reflects the f undamental pathophysiological sequelae of brain injury seen in clinical neurotraumatology.…”
Section: Discussionmentioning
confidence: 99%
“…Theories of glaucoma pathogenesis include mechanodistortion of the optic nerve at its exit from the eyeball affecting RGC transport mechanisms, and compression of optic nerve head microvasculature compromising neuronal circulation (reviewed by Quigley, 1995). It has been reported that inhibition of retrograde axonal flow can only partly explain RGC loss post axotomy (Fagiolini et al, 1997). There is evidence from other studies that RGC loss may be mediated independently of these mechanisms (Radius 1981;Johansson 1983Johansson , 1988.…”
mentioning
confidence: 99%